The Recent Financial Turmoil : Initial Assessment, Policy Lessons, and Implications for Fund Surveillance. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
In response to the IMFC's October 2007 communique, IMF staff has sought to assess the causes of the present turbulence and draw tentative lessons in order to inform its future bilateral and multilateral surveillance work. This effort has involved close collaboration with the Financial Stability Forum (FSF) and its working groups, as well as consultation with the private sector, national authorities, standard setters, and other bodies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet